Creating accountable hospital service areas in China: a case analysis of health expenditure in the metropolis of Chengdu - Jay Pan; Peiya Cao; Xiaoshuang Zhao; Yili Yang (BMJ Open)
Objectives To delineate hospital service areas (HSAs) using the Dartmouth approach in China and identify the hypothesised demand-side, supply-side and region-specific factors of health expenditure within HSAs.Design Population-based descriptive study.Setting We selected the metropolis of Chengdu, one of the three most populous cities in China as a case for the analysis, where approximately 16.33 million residents living.Participants Individual-level in-patient discharge records (n=904 298) during the fourth quarter of 2018 (from 1 September to 31 December) were extracted from Sichuan Health Commission. Cases of non-residents of Chengdu were excluded from the datasets.Methods We conducted three sets of analyses: (1) apply Dartmouth approach to delineate HSAs; (2) use Geographic Information System (GIS)-based method to demonstrate health expenditure variations across delineated HSAs and (3) employ a three-level multilevel linear model to examine the association between health expenditure and demand-side, supply-side and region-specific factors.Results A total of 113 HSAs with a median population of 60 472 (ranging from 7022 to 827 750) was delineated. Total in-patient expenditure per admission varied more than threefold across HSAs after adjusting for age and gender. Apart from a list of demand-side factors, an increased number of physicians, healthcare facilities at higher levels and for-profit healthcare facilities were significantly associated with increased total in-patient expenditures. At the HSA level, the proportion of private healthcare facilities located in a single HSA was associated with increased total in-patient expenditure generated by that HSA, while the increased number of healthcare facilities in a HSA was negatively associated with the total in-patient expenditures.Conclusion HSAs were delineated to help establish an accountable healthcare delivery system, which serves as local hospital markets to provide in-patient healthcare via connecting demanders with suppliers inside particular HSAs. Policy-makers should adopt HSAs to identify variations of total in-patient expenditures among different areas and the potential associated factors. Findings from the HSA-based analysis could inform the formulation of relevant health policies and the optimisation of healthcare resource allocations.